2018
DOI: 10.1002/app.47094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular structures on static and dynamic compression properties of clay and amphiphilic clay/carbon nanofibers used as fillers in UHMWPE/composites for high‐energy‐impact loading

Abstract: Three different ultrahigh‐molecular‐weight polyethylene (UHMWPE)–clay nanocomposites (Muscovite, Cloisite 30B and amphiphilic clay/carbon nanofibers) were investigated with the nanocomposite nanomorphology studied before and after dynamic mechanical compressive tests at high strain rates. Their material structure and thermal properties were investigated using techniques such as step‐scan differential scanning calorimetry, split Hopkinson pressure bar, synchrotron small angle X‐ray scattering (SAXS), and dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Because of the versatile properties of clay, it also attracts many researchers and is used as filler in the preparation of composites. [12] Recently, the clay minerals were successfully loaded into the polymeric matrix after modifying the surface of clay with suitable linkers, which eliminate the compatibility issues. Naturally available clays such as kaolinite, vermiculite, montmorillonite (MMT) and pyrophyllite are widely used as catalysts for many organic reactions and transformations, namely dimerization, dehydration, isomerization, Friedel Crafts reactions, several photochemical reactions, and so forth.…”
mentioning
confidence: 99%
“…Because of the versatile properties of clay, it also attracts many researchers and is used as filler in the preparation of composites. [12] Recently, the clay minerals were successfully loaded into the polymeric matrix after modifying the surface of clay with suitable linkers, which eliminate the compatibility issues. Naturally available clays such as kaolinite, vermiculite, montmorillonite (MMT) and pyrophyllite are widely used as catalysts for many organic reactions and transformations, namely dimerization, dehydration, isomerization, Friedel Crafts reactions, several photochemical reactions, and so forth.…”
mentioning
confidence: 99%
“…Compressive strength, at different filler weight contents and strain rates of PP/S, [112] PP/ZnO, [57] E/S, [113] E/ GO, [114] E/CNT, [115] PE/GNP, [116] PE/C, [117] E/PS, [118] and PE/SD. [119] C, clay; E, epoxy; GO, graphene oxide; GNP, graphene nanoplatelets; PE, polyethylene; PP, polypropylene; PS, polystyrene microspheres; S, silica; SD, sawdust; ZnO, zinc oxide F I G U R E 1 4 Compressive modulus (measured at a strain rate of 10 3 s À1 ), at different filler weight content of PP/S, [112] PP/ ZnO, [57] E/GO, [114] PE/C, [117] E/PS, [118] and PE/SD, [119] and E/GNP.…”
Section: Dynamic Mechanical Performance Of Composites 41 | Polymers Filled With Particlesmentioning
confidence: 99%
“…Compressive strength, at different filler weight contents and strain rates of PP/S, [112] PP/ZnO, [57] E/S, [113] E/ GO, [114] E/CNT, [115] PE/GNP, [116] PE/C, [117] E/PS, [118] and PE/SD. [119] C, clay; E, epoxy; GO, graphene oxide; GNP, graphene nanoplatelets; PE, polyethylene; PP, polypropylene; PS, polystyrene microspheres; S, silica; SD, sawdust; ZnO, zinc oxide F I G U R E 1 4 Compressive modulus (measured at a strain rate of 10 3 s À1 ), at different filler weight content of PP/S, [112] PP/ ZnO, [57] E/GO, [114] PE/C, [117] E/PS, [118] and PE/SD, [119] and E/GNP. [120] C, clay; E, epoxy; GO, graphene oxide; GNP, graphene nanoplatelets; PE, polyethylene; PP, polypropylene; PS, polystyrene microspheres; S, silica; SD, sawdust; ZnO, zinc oxide the strength of the particle-matrix interfacial bonding strength is more important than the quality of the particle dispersion, in terms of an enhancement in mechanical properties.…”
Section: Dynamic Mechanical Performance Of Composites 41 | Polymers Filled With Particlesmentioning
confidence: 99%
“…5 Therefore, adding compatibilizing agents (CAs) such as maleic anhydride (MA), which act on the interface between organic and inorganic surfaces, is an option to increase adhesion between materials, especially in cases of polar to non-polar substances. 6 Dias et al 7 showed that the incorporation of clay montmorillonite Cloisite 30B in the molten state in an ultra-high density polyethylene matrix, without the use of a CA, resulted in reduced mechanical and dynamic mechanical properties, if compared to those found for the pure polymer. On the other hand, an increase in the filler-matrix adhesion and the consequent improvement in the mechanical properties of the polyethylene and bentonite clay maleinized composite was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Although substantial changes can be realized with small amounts of Gr (<3 wt.%), 11,13,17 such as increased impact resistance and energy absorption capacity, clays are usually used at 1 to 5 wt.%. 4,7,9,10 For this reason, this work aims to evaluate the effect of the combination of montmorillonite Cloisite 30B organically modified montmorillonite (OMt) (0, 1, 3, and 5 wt.%) and GNP (ranged from 0 to 50 wt.% of the OMt content) in maleinized highdensity polyethylene (HDPE) matrix on the properties obtained from the SHPB dynamic compression test.…”
Section: Introductionmentioning
confidence: 99%